2021
DOI: 10.2147/cmar.s327381
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Levonorgestrel-Resistant Endometrial Cancer Cells

Abstract: Background: Endometrial cancer (EC) is the most common gynaecologic malignancy in the developed world, and incidence is increasing in premenopausal women. The levonorgestrel intrauterine system (LNG-IUS) is gaining traction as an alternative treatment for hyperplasia and early-stage EC for women who are unable to undergo surgery. Thirty to 60% of the women do not respond to this treatment, making the unknown mechanisms of levonorgestrel (LNG) resistance a critical obstacle for the conservative management of EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…We previously characterized the LNG resistant cell lines used in the current study, and investigated potential predictive biomarkers of LNG resistance found in the literature. KLF4 and SATB2 were identified as significantly differentially expressed between LNG resistant and non‐resistant EC cell lines 14 . It is important to note that these genes did not appear in the top significant DEGs in the current study.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We previously characterized the LNG resistant cell lines used in the current study, and investigated potential predictive biomarkers of LNG resistance found in the literature. KLF4 and SATB2 were identified as significantly differentially expressed between LNG resistant and non‐resistant EC cell lines 14 . It is important to note that these genes did not appear in the top significant DEGs in the current study.…”
Section: Discussionmentioning
confidence: 60%
“…Yang et al, conducted a study using the GSE121367 data set from Li et al 26 and SATB2 were identified as significantly differentially expressed between LNG resistant and non-resistant EC cell lines. 14 It is important to note that these genes did not appear in the top significant DEGs in the current study. We did however, observe a nonsignificant increased FC in KLF4 in both cell lines.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This may be in part explained by the fact that women over the age of 50 years had a higher rate of endometrial cancer (25/41, 61%) compared with those younger than 50 years (19/35, 54%). Endometrial cancer is less likely to respond than AEH, 29 and histopathological features that indicate more aggressive disease are predictive of treatment failure 28,30 . Serum HE4 is associated with clinical markers of disease severity including myometrial invasion of 50% or more, FIGO stage, lymphovascular space invasion and tumour size, 13,15,31–36 offering a potential explanation for its association with treatment failure and highlighting the importance of identifying non‐responders before treatment.…”
Section: Discussionmentioning
confidence: 99%